Effect of Degree of Milling on the Quality of Daohuaxiang Rice and Physicochemical Properties of Instant Rice - Lele LU; Qin SHEN; Shuangjing LANG; Di YAO; Lidong WANG; Changyuan WANG (Shipin gongye ke-ji)
To enhance the edible and nutritional quality of rice, four types of rice were prepared using Daohuaxiang rice as the raw material: white rice (0.21% bran degree), reasonably well-milled rice Ⅰ (2.15% bran degree), reasonably well-milled rice Ⅱ (6.67% bran degree), and brown rice. The study analyzed the characteristics of rice processing, nutrition, and edible quality, and evaluated the rehydration properties and sensory quality of instant rice. The results indicated that there was no significant difference in whiteness between rice Ⅰ, which was reasonably well-milled, and rice Ⅱ, also reasonably well-milled. However, the percentages of broken rice decreased by 8.91% and 19.85%, respectively. The contents of fat, protein, and vitamin B1 in well-milled rice Ⅱ were 6.6 times, 1.14 times, and 3.58 times greater than those found in white rice, respectively. Additionally, these levels were significantly higher than those observed in well-milled rice Ⅰ (P<0.05). The cooking quality and taste of rice Ⅰ, rice Ⅱ, and white rice were not significantly different, and all were superior to brown rice. The water absorption and hardness of rice Ⅰ, rice Ⅱ, and white rice stabilized after rehydration for 8 min, with water content ranging from 153% to 155%, which was 92.5% higher than that of brown rice. The aroma of rice Ⅱ was better than that of rice Ⅰ and white rice. However, there was minimal difference in sensory scores between white rice and rice Ⅰ. In conclusion, the appearance quality of rice diminished with an increase in bran degree, while some nutritional qualities exhibited an inverse trend. Nevertheless, the variation in bran degree had no significant effect on eating quality, cooking quality, rehydration characteristics, and sensory scores. Rice with a bran degree close to the upper limit of 7% in reasonably well-milled varieties offers significant advantages in terms of utilization, nutrition, and health. This finding provides theoretical support for the development of nutritionally balanced, reasonably well-milled rice and instant rice products.